Implementasi Program GERMAS untuk Meningkatkan Personal Hygiene dan PHBS Lansia Secara Berkelanjutan - Herniwanti Herniwanti; Oktavia Dewi; Emy Leonita; Rafni Nashabila (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This study aimed to improve personal hygiene practices and Perilaku Hidup Bersih dan Sehat (PHBS) among elderly individuals through a structured health education program integrated with Indonesia’s national Gerakan Masyarakat Hidup Sehat (GERMAS). The program focused on increasing awareness, encouraging healthy daily habits, and supporting independence among older adults. Methodology/Approach: The program was implemented in Sungai Kamuyang Village, West Sumatra, using a community-based home-visit approach. Health education was delivered through brief counseling and demonstrations of personal hygiene practices, accompanied by the distribution of hygiene kits. Observations of household sanitation conditions and daily hygiene routines were conducted, and data were collected through short interviews and field notes with assistance from local health cadres. Results/Findings: The intervention resulted in positive behavioral changes. Approximately 85% of participants demonstrated improved understanding of PHBS principles, 80% practiced regular personal hygiene routines, and 60% engaged in light physical activity. However, only 40% reported routine health check-ups, and nearly half of the households still lacked adequate sanitation facilities, indicating ongoing environmental and service-related barriers. Conclusions: The program effectively improved elderly hygiene practices and PHBS awareness, though barriers like sanitation and health check-ups remain. Further research is needed. Limitations: The study was limited by a small sample size and a short implementation period, which may restrict the generalizability of the findings. Contributions: This study provides practical evidence for public health practitioners, community health workers, and policymakers on the effectiveness of home-based education integrated with GERMAS in promoting healthy behaviors among the elderly.